Seasonal migrations, population dynamics and age structure of the Spotted Flycatcher Muscicapa striata (Aves, Passeriformes) according to trapping and ringing data for sixty-four years (1957–2020) in the Eastern Baltic - Payevsky, Vladimir A.; Shapoval, Anatoly P. (Acta Biologica Sibirica, 2024)
The results of the trapping and ringing of the Spotted Flycatcher at the “Fringilla” field station in the Courish (Curonian) Spit, Eastern Baltic, for the period 1957–2020, in the number of 7984 individuals are presented. The annual number of birds caught has varied for 64 years, while the period since the mid–1980s has been characterized by a downward trend in numbers. Due to the "coastal effect", the proportion of adult birds averaged 3%, varying by year from 1% to 14%. The recoveries of our rings during the spring arrival and breeding of birds are concentrated in the coastal northern parts of the Baltic Sea and the Gulf of Bothnia, in the territories of Denmark, Sweden and Finland. The recoveries of our rings during the autumn migration are from Italy. The average daily speed of autumn movement is 66–87 km per day. The age (in years) at the discovery time of the bird with the ring was from one to five years old.